Praznična glasba kapitljev na Krku in njena recepcija pri srednješolcih - Ilijić, Saša (visokošolska dela, 2020)
This dissertation deals with the attitude of high school youth (ages 14 to 18) toward the traditional music from the island of Krk in the context of patron saint celebrations in former bodies of the church, called chapters. The towns are: Omišalj, Dobrinj, Vrbnik and Baška. The research consists of two parts, theoretical and empirical. The former is divided into three parts: sociolinguistic, geo-cultural and musical. The main, empirical part of this dissertation focuses on discovering how the young population of the island feels toward the traditional music. The empirical research was carried out via a questionnaire, handed out to students at Hrvatski kralj Zvonimir high school centre in the town of Krk. Based on four hypotheses, we try to establish the external factors that contribute to either positive or negative relationship of the youth toward the traditional music.
Keywords: Croatian music; disertacije; dissertations; ethnomusicology; etnomuzikologija; Glagolitic chanting; glagoljaško petje; high school students; hrvaška glasba; intangible cultural heritage; kanat po domaću; Krk island; mot; nesnovna kulturna dediščina; nota; otok Krk; Recepcija; safeguarding; sociologija glasbe; sociology of music; srednješolci; tradicija; Tradicijska glasba; tradition; varovanje